2019
DOI: 10.1155/2019/1471728
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis and Application of Nitrogen-Doped Graphene Quantum Dots on Brilliant Blue Detection

Abstract: Nitrogen-doped graphene quantum dots had been successfully synthesized and characterized by using transmission electron microscope, X-ray photoelectron spectroscopy, absorbance spectrum, fluorescence emission spectrum, and fluorescence decay curve. TEM results indicated that the diameters of the as-prepared nitrogen-doped graphene quantum dots were in the range of 2 - 5 nm and the lattice space is about 0.276 nm; Raman spectrum result indicated that there were two characteristic peaks, generally named D (~1408… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 34 publications
3
10
0
Order By: Relevance
“…Тhe obtained LOD is evaluated to be 0.187 nmol L −1 (R 2 = 0.974) and 153 nmol L −1 (R 2 = 0.984) for p-GQDs and GQDs-200-EDA, respectively. The LOD values are in a similar range with recently published results [71,72]. A near 1 determination coefficient (R 2 ) qualifies p-GQDs and GQDs-200-EDA nanoparticles as efficient quenchers.…”
Section: Detection Of Cu(ii) Ionssupporting
confidence: 87%
“…Тhe obtained LOD is evaluated to be 0.187 nmol L −1 (R 2 = 0.974) and 153 nmol L −1 (R 2 = 0.984) for p-GQDs and GQDs-200-EDA, respectively. The LOD values are in a similar range with recently published results [71,72]. A near 1 determination coefficient (R 2 ) qualifies p-GQDs and GQDs-200-EDA nanoparticles as efficient quenchers.…”
Section: Detection Of Cu(ii) Ionssupporting
confidence: 87%
“…A previous study reported that C-dots derived via pyrolytic treatment (1 h, 250 °C) of CA/urea mixture with f CA/urea = 1:3 shows τ avg = 6.7 ns, while hydrothermal treatment of the same precursor mixture resulted in the generation of N-GQDs with τ avg = 8.1 ns 31 , 67 . At the same time, a single exponential PL decay with lifetime of 6.4 ns has been demonstrated for CTA 68 , while C-dots are known to exhibit multi-exponential delay stemming from heterogeneous emitting states in a single C-dot or within a larger C-dot ensemble 69 .…”
Section: Photoluminescence Properties In Watermentioning
confidence: 93%
“…A previous study reported that C-dots derived via pyrolytic treatment (1h, 250°C) of CA/urea mixture with fCA/urea=1:3 shows τavg=6.7 ns, while hydrothermal treatment of the same precursor mixture resulted in the generation of N-GQDs with τavg=8.1 ns [37,67]. At the same time, a single exponential PL decay with lifetime of 6.4 ns has been demonstrated for CTA [68], while C-dots are known to exhibit multi-exponential delay stemming from heterogeneous emitting states in a single C-dot or within a larger C-dot ensemble [69].…”
Section: Photoluminescence Properties In Watermentioning
confidence: 84%